2014
DOI: 10.1165/rcmb.2013-0103oc
|View full text |Cite
|
Sign up to set email alerts
|

High-Density Lipoproteins Potentiate α1-Antitrypsin Therapy in Elastase-Induced Pulmonary Emphysema

Abstract: Several studies report that high-density lipoproteins (HDLs) can carry α1-antitrypsin (AAT; an elastase inhibitor). We aimed to determine whether injection of exogenous HDL, enriched or not in AAT, may have protective effects against pulmonary emphysema. After tracheal instillation of saline or elastase, mice were randomly treated intravenously with saline, human plasma HDL (75 mg apolipoprotein A1/kg), HDL-AAT (75 mg apolipoprotein A1-3.75 mg AAT/kg), or AAT alone (3.75 mg/kg) at 2, 24, 48, and 72 hours. We h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 54 publications
2
45
0
Order By: Relevance
“…In this regard, a recent study has shown that AAT bound to high-density lipoprotein and when administered in a mouse model of pulmonary emphysema afforded greater protection from emphysema than AAT alone (82). The advantages included a reduction in airway neutrophil and macrophage counts, decreased IL-6, MCP-1, and TNF-a levels, as well as a reduction in MMP activity and degradation of fibronectin (82). AAT can also interact with the iron atom in heme (83) and CD16b on membrane lipid rafts of circulating neutrophils (29).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, a recent study has shown that AAT bound to high-density lipoprotein and when administered in a mouse model of pulmonary emphysema afforded greater protection from emphysema than AAT alone (82). The advantages included a reduction in airway neutrophil and macrophage counts, decreased IL-6, MCP-1, and TNF-a levels, as well as a reduction in MMP activity and degradation of fibronectin (82). AAT can also interact with the iron atom in heme (83) and CD16b on membrane lipid rafts of circulating neutrophils (29).…”
Section: Discussionmentioning
confidence: 99%
“…The AAT concentrations in serum may vary depending on the condition of an individual, with normal values ranging from 1.5 to 3.5 g/L (or from 20 to 48 μM). The amount of research on AAT-associated renal diseases is still very small (Moreno et al, 2014;Ortiz et al, 2014;Zager et al, 2014).…”
Section: Patterns and Types Of Urine Specific Proteinsmentioning
confidence: 99%
“…For example, biological activities of A1AT can be modified due to interactions with lipid moieties, in which A1AT was found in association with cell membrane lipid rafts (19,20) and was detected in complexes with low-density lipoproteins (LDLs) and high-density lipoproteins (HDLs). (21,22) The binding of A1AT to HDL augments its protective effect in a mouse model of elastase-induced pulmonary emphysema. (22) We recently reported that A1AT purified from human plasma binds polyunsaturated fatty acids (FAs) like α-linoleic and oleic acid, and that only FA-bound forms of A1AT increase the expression and release of ANGPTL4 in human bloodadherent monocytic cells and in primary human lung microvascular endothelial cells.…”
Section: Caspase-1 Inhibition Assaymentioning
confidence: 99%
“…(21,22) The binding of A1AT to HDL augments its protective effect in a mouse model of elastase-induced pulmonary emphysema. (22) We recently reported that A1AT purified from human plasma binds polyunsaturated fatty acids (FAs) like α-linoleic and oleic acid, and that only FA-bound forms of A1AT increase the expression and release of ANGPTL4 in human bloodadherent monocytic cells and in primary human lung microvascular endothelial cells. (23,24) The above functional differences between FA-free and FA-bound forms of A1AT led us to hypothesize that these 2 forms may express distinct immunomodulatory activities during neutrophil activation.…”
Section: Caspase-1 Inhibition Assaymentioning
confidence: 99%